PROFIL PASIEN COVID-19 DI RUMAH SAKIT UNIVERSITAS ANDALAS - Putri, Azhara Dhiya Yosse; Lestari, Yuniar; Susanti, Restu; Afriant, Rudy; Putra, Syandrea Prima; Yusri, Elfira (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS- CoV-2 virus. The outcomes of COVID-19 patients were found to be influenced by the presence of comorbidities of the patient. Furthermore, this will affect the healing process in the patient itself. The most common comorbidity in COVID-19 patients is hypertension followed by diabetes mellitus. Hypertension is mentioned as the predominant factor of COVID-19 infection. Objective: This study aims to determine the profile of COVID-19 patients with hypertension. Methods: The type of this research is observational descriptive which was conducted in October 2021 – November 2022 at the Medical Record Installation of Rumah Sakit Universitas Andalas. This study was conducted using a total sampling technique with a total sample of 161 patient. Results: The results showed that the frequency of female was more than male (60.9:39.1). The frequency of >50 years old is almost the same as 50 years old (50.9:49.1). There are more patients without comorbid hypertension than patients with comorbid hypertension (64.6:35.4). Conclusions: There are more COVID-19 patients treated at Andalas University Hospital aged 50 years with female sex and more patients without hypertension comorbid.